Fanatic and Fanaticism from the Perspective of Islamic Law and Islamic Education Perspective - Husnawadi, Husnawadi; Nasri, Ulyan (Jurnal Ilmiah Profesi Pendidikan, 2023)
This study aims to investigate the phenomena of fanaticism and fanatical behavior from the perspectives of Islamic Law and Islamic Education. Data were collected through a review of classical and contemporary texts in Islamic law and education, as well as an analysis of relevant empirical studies. The data analysis technique employed a qualitative approach focusing on text interpretation and key concepts related to fanaticism. The results indicate that fanaticism in Islamic Law and Islamic Education encompasses complex dimensions, including psychological, social, and theological factors. The implications of this research underscore the need for a holistic approach to understanding and addressing fanaticism, involving educational, social, and legal efforts. Islamic education can play a key role in instilling moderate values, tolerance, and deep understanding of religious teachings. Legally, it is important to consider principles of justice and freedom in responding to fanatical behavior while upholding principles that underpin diversity and tolerance in society. In conclusion, a profound understanding of fanaticism from the perspectives of Islamic Law and Islamic Education can aid in formulating effective strategies to address this challenge in contemporary society.